The formation of A-DNA in NaDNA films is suppressed by netropsin. - Fritzsche, H (1992)
Oriented films of NaDNA complexed with netropsin were studied with deuterium nuclear magnetic resonance (2H NMR), X-ray diffraction and ultraviolet (UV) linear dichroism to obtain information about the influence of netropsin on the structural arrangement of the DNA bases and on the B-A transition. The results of these studies clearly demonstrate a strong suppression of the formation of A-DNA at relative humidities (RHs) down to about 50%. The suppression was complete in the NaDNA-netropsin complex studied with 2H NMR which had a netropsin input ratio, r, of 0.22 drug/base pair. The sample used for UV linear dichroism had a similar input ratio while the X-ray diffraction samples had input ratios between 0.033 and 0.39 drug/base pair. Together, the results of these studies are in agreement with previous infrared (IR) linear dichroism studies of the conformation of the sugar-phosphate backbone in NaDNA-netropsin complexes, which showed that the B-A transition is suppressed for r-values down to approximately 0.1 drug/base pair (Fritzsche, H., Rupprecht, A. and Richter, M., Nucleic Acids Res. 12 (1984) 9165-9177).